2012
DOI: 10.1155/2012/264017
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disorders and Steatosis in Patients with Chronic Hepatitis C: Metabolic Strategies for Antiviral Treatments

Abstract: It has been reported that hepatitis C virus (HCV) infection is closely associated with hepatic metabolic disorders. Hepatic steatosis and insulin resistance are both relatively common in patients with chronic hepatitis C. Recent investigations suggest that HCV infection changes the expression profile of lipid-metabolism-associated factors in the liver, conferring advantages to the life cycle of HCV. Moreover, insulin resistance and steatosis are independent predictors of impaired response to antiviral treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
0
6
0
1
Order By: Relevance
“…This in turn deregulates fatty acid synthesis and leads to hepatic steatosis. In parallel, the HCV core protein increases the activity of peroxisome proliferator-activating receptor (PPAR)–alpha and gamma in hepatocytes contributing to deregulation of fatty acid beta-oxydation and insulin sensitivity (for a review see [46]). Finally, Fujino et al demonstrated that lipid metabolism genes like the SREBP family genes expression are modified through this mechanism [26].…”
Section: Lipids Apolipoproteins and Hcv Pathogenesismentioning
confidence: 99%
“…This in turn deregulates fatty acid synthesis and leads to hepatic steatosis. In parallel, the HCV core protein increases the activity of peroxisome proliferator-activating receptor (PPAR)–alpha and gamma in hepatocytes contributing to deregulation of fatty acid beta-oxydation and insulin sensitivity (for a review see [46]). Finally, Fujino et al demonstrated that lipid metabolism genes like the SREBP family genes expression are modified through this mechanism [26].…”
Section: Lipids Apolipoproteins and Hcv Pathogenesismentioning
confidence: 99%
“…The best characterized of these receptors are the cannabinoid 1 receptor and the cannabinoid 2 receptor . Although traditionally associated with the central nervous system (CNS), cannabinoid receptors in hepatocytes are increasingly being recognized as key mediators of fatty liver and associated insulin resistance caused by high‐fat diet , viral hepatitis and ethanol intake . Additionally, cannabis smoking has been shown to be a risk factor for hepatic steatosis and, in a separate study, patients with non‐alcoholic fatty liver disease were found to have a 34.2 ± 9.7‐fold increase in the amount of hepatic CB 1 R mRNA compared with patients without liver pathology .…”
Section: The Role Of Cannabinoid Receptors In Fatty Livermentioning
confidence: 99%
“…Additionally, HCV infection induces activation of sterol regulatory element binding protein (SREBP), the transcription factor responsible for lipogenesis [ 20 , 21 , 22 ]. Downregulation of carnitine palmitoyltransferase expression may additionally increase steatosis by inhibition of beta-oxidation [ 23 ]. Overproduction of lipid droplets has also been observed in HCV-transfected cells.…”
Section: Lipid Phenotype Of Chronic Hcv Patientsmentioning
confidence: 99%